Aislamiento y crecimiento de cepas ambientales de Pseudomonas aeruginosa, Bacillus sp. Aspergillus niger y Penicillium sp. aisladas de talleres de mecánica como potenciales biodegradadoras de hidrocarburos derivados de petróleo Iquitos Perú 2024 - Tapayuri Rengifo, Kervin Brayan (2025)
The aim of this study was to evaluate the growth capacity of environmental strains of Pseudomonas aeruginosa, Bacillus sp., Aspergillus niger and Penicillium sp. isolated from mechanical workshops in Iquitos, in the presence of petroleum hydrocarbons. The experimental design was explanatory, with a longitudinal approach and non-probabilistic sampling, dividing the strains into three groups: control, experimental 1 (1% diesel) and experimental 2 (2% diesel). Samples were taken from surfaces in the workshops and cultured on media with diesel (TSA and PDA) as the sole carbon source. The results showed that Pseudomonas aeruginosa increased significantly in proliferation, with Colony Forming Units (CFU) increasing from 112.3 CFU/m³ in the control (T0) to 437.3 CFU/m³ in the 2% diesel treatment (T2). Bacillus sp. also grew, but more modestly, reaching 140 CFU/m³ at T2. As for the fungi, Aspergillus niger showed superior radial growth, although, it decreased from 4.92 cm in the control (T0) to 3.31 cm in T2, while Penicillium sp. maintained limited growth with 1.22 cm in T0 and slight variation in the diesel treatments. These results suggest that, although bacteria, especially Pseudomonas aeruginosa, have a greater potential for bioremediation of diesel-contaminated soils, fungi also have a role in this process, but are more sensitive to high concentrations of contaminants. The study highlights the importance of Pseudomonas aeruginosa and Aspergillus niger as key species for hydrocarbon biodegradation in contaminated soils.